Traditional ecological knowledge reveals the extent of sympatric lake trout diversity and habitat preferences - Kia Marin; Andrew Coon; Dylan J. Fraser (Ecology and Society, 2017)
Multidisciplinary approaches to conservation have become increasingly important in northern regions. Because many First Nations communities have relied on freshwater fish populations for essential food over millennia, community members often possess traditional ecological knowledge (TEK). We consulted Cree First Nation fishers to collate TEK for one of Canada's most important subsistence fishes (lake trout) in Québec's largest lake (Mistassini, 2335 km2). We further integrated TEK with what was regionally known scientifically about the species, toward effective fisheries conservation. Cree fishers described a richer diversity of sympatric lake trout forms than did scientific research that was conducted simultaneously, based on color, size, fin accent patterns, scale texture and depth, and spatial preferences. Traditional ecological knowledge also provided descriptions of lake trout seasonal movements, spawning locations, and reproductive timing that were not captured by scientific research, and highlighted several concerns or temporal changes of import to future management initiatives. Our study highlights the wealth of TEK on harvested species in First Nations communities. It further illustrates how TEK can reveal not only distinctions within species of relevance to natural resource management and taxonomy, but also informs upon the extent of such population differentiation, thereby providing important conservation benefits for remote and northern regions.